Development and Characterization of a Diamine Oxidase-Based Histamine Biosensor - Ching, Mai Keow (2006)
Histamine levels have been suggested as a rapid fish spoilage indicator. Therefore, histamine biosensors based on immobilization of diamine oxidase (DAO) in photocurable poly (2-hydroxyethyl methacrylate) (photoHEMA) film was developed. Histamine was oxidized by immobilized DAO at 0.35 volt on the surface of carbon-paste screen-printed electrode (SPE) versus conventional Ag/AgCl reference, and with platinum rod as a counter electrode, which named as macro electrode system histamine biosensor. No leaching of the immobilized DAO was observed during histamine detection using the biosensor. The optimized histamine biosensor displayed a linear response over the range of 0 to 60 ppm histamine with correlation coefficient (R2) equals to 0.9946 (RSD < 11.19%). The sensitivity obtained was 5.56 nA ppm-1 and the limit of detection was 0.65 ppm of histamine with the response time of 50 seconds. The histamine biosensor exhibited repeatability and reproducibility characteristic with RSD values equals to 14.06 and 7.80% (n = 10) respectively. The histamine biosensor was applied to determine histamine in tiger prawns (Penaeus monodon) and the results were agreeable with a conventional high performance liquid chromatography (HPLC) method, where a correlation of R2 = 0.9612 (Y = 0.9614 x + 5.5813) was obtained. The developed histamine biosensor showed recovery of added histamine in the range of 93.11 to 100.58%. Home made miniaturized histamine biosensor (30 mm x 10 mm) was then developed by screen-printed of carbon as working and counter electrodes together with Ag/AgCl reference electrode on the polyester substrate {named SPE (i)}. Miniaturized histamine biosensor with SPE (i) operated at 0.25 volt exhibited a linear range from 0 to 100 ppm of histamine with R2 = 0.9577 (RSD < 9%) and sensitivity of 0.03 nAppm-1 with the limit of detection of 2.46 ppm of histamine. The miniaturized histamine biosensor with a SPE (ii) was operated at 0.35 volt and it showed a linear range from 0 to 50 ppm histamine with R2 of 0.9766 (RSD < 16%) and sensitivity of 0.40 nAppm-1. The limit of detection of histamine was 4.64 ppm. The miniaturized SPE (i) was then modified with K3Fe(CN)6 and operated at 0.35 volt. This biosensor could detect the histamine in the linear range of 0 to 80 ppm with the R2 = 0.9931 and sensitivity 5.31 nAppm-1. The limit of detection for this modified histamine biosensor was 2.11 ppm histamine.